Konstruksi Pendidikan Karakter dalam Budaya Mandailing dan Angkola di Provinsi Sumatera Utara: Construction of Character Education in Mandailing and Angkola Culture in North Sumatra Province - Rahmat Hidayat (Society, 2020)
This research aims to describe the construction and character education model in Mandailing and Angkola tribes in North Sumatra Province. This research uses a qualitative method with a case study approach, a research method on individuals, groups, organizations, and specific institutions. Instruments or data collection tools used in this research are (1) observation; (2) in-depth interview; (3) document study. This research uses a method known as ethnography or participant observation. The result shows that Mandailing and Angkola tribes’ characters building through 1) Socialization, 2) Enculturation, and 3) Internalization. Socialization including education, clarification, and motivation. Meanwhile, enculturation including imitation, habituation, and evaluation. Construction of education in Mandailing and Angkola tribes through habits, traditions, culture, and Islamic values. Character building in children is an effort to encourage self-awareness and concern for tradition, culture, and preserve local wisdom to sustain from generation to generation. Also, several efforts to preserve culture have been made by collaborating with schools, traditional and religious leaders to combine local wisdom and culture into schools’ curriculum and extracurricular activities.